Simultaneous Left Ventricular Aneurysm and Ventricular Septal Rupture Complicating Delayed STEMI Presentation: A Case-Based Review of Post-MI Mechanical Complications Amid the COVID-19 Pandemic - Muhammad Hassan Naeem Goraya MD; Sidra Kalsoom MD; Talal Almas BS; Muhammad Kashif Amin MD; Nadeem Hussain MD; Junaid Rasul Awan MD; Maryam Ehtesham BS; Muhammad Ali Niaz BS; Hafeez Ul Hassan Virk MD; Steven J. Filby MD (SAGE Publishing, 2021)
Amid the coronavirus disease 2019 (COVID-19) pandemic, there is an unprecedented increase in public avoidance of hospitals predominantly driven by fear of contracting the virus. Recent publications highlight a re-emergence of rare post-myocardial infarction complications. While mechanical complications are infrequent in the era of primary percutaneous coronary intervention, they are associated with high mortality rates. The concurrent occurrence of mechanical complications such as left ventricular aneurysm and ventricular septal rupture is an extremely rare entity. We hereby delineate a unique case of a 53-year-old Caucasian male who underwent successful concomitant closure of a ventricular septal rupture, left ventricular aneurysmectomy, and 3-vessel coronary artery bypass grafting. Due to a delayed initial presentation owing to the patient's fear of contracting COVID-19, the surgery was carried out 3 months after the myocardial infarction. His postoperative evaluation confirmed normal contractility of the left ventricle and complete closure of the ventricular septal rupture. Six months postoperatively, the patient continues to do well. We also present a literature review of the mechanical complications following delayed presentation of myocardial infarction amid the COVID-19 pandemic. This article illustrates that clinicians should remain cognizant of these extremely rare but potentially lethal collateral effects during the ongoing global public-health challenge. Furthermore, it highlights a significant concern regarding the delay in first medical contact due to the reluctance of patients to visit the hospital during the COVID-19 pandemic.